Lipase-catalysed polymerization of eutectic mixtures - Freitas, David (2023)
Supporting Information available at: https://chemistry-europe.onlinelibrary.wiley.com/action/downloadSupplement?doi=10.1002%2Fcssc.202202374&file=cssc202202374-sup-0001-misc_information.pdf